The majority of circulating platelet-derived microparticles fail to bind annexin V, lack phospholipid-dependent procoagulant activity and demonstrate greater expression of glycoprotein Ib - Connor, David Ewan; Exner, Thomas; Ma, David Dang Fung; Joseph, Joanne Emily (Thrombosis and Haemostasis, 2010)
It has been widely accepted that microparticles expose phosphatidylserine which in turn binds annexin V. It was the objective of this study to compare the antigenic characteristics and phospholipid-dependent procoagulant activity of annexin V positive and -negative subpopulations of platelet-derived microparticles. Annexin V positive and -negative microparticles were identified and characterised using flow cytometry and procoagulant activity was measured by a phospholipid-dependent assay (XACT). In unstimulated platelet-poor plasma, 80% of platelet-derived microparticles failed to bind annexin V. Varying the assay constituents (buffer, calcium and annexin V concentration) did not alter annexin V binding. The proportion of microparticles that bound annexin V was dependent upon the agonist, with physiological agonists such as collagen resulting in fewer annexin V binding microparticles than non-physiological agonists such as ionophore. CD42b (glycoprotein Ib) expression was significantly decreased and CD62p and CD63 expression were significantly increased in annexin V positive compared to annexin V negative subpopulations. There was no significant difference in CD41, CD61, CD42a and CD40L expression between annexin V positive and -negative subpopulations. A significant correlation between annexin V binding and XACT was found (p=0.033). Annexin V inhibited greater than 95% of phospholipid activity, suggesting that annexin V binding was a true reflection of procoagulant activity. The majority of platelet-derived microparticles in unstimulated plasma failed to bind annexin V and showed significantly increased levels of CD42b compared to annexin V positive events. Phospholipid-dependent procoagulant activity is limited to the annexin V positive subpopulation and is agonist-dependent. The significance of annexin V negative microparticles is unclear, however, it is possible that they possess other activities aside from procoagulant phospholipid activity.
Keywords: Annexin V; flow cytometry; microparticles; phosphatidylserine; XACT